Organizational Adaptive Responses to External Pressures: Employee Perceptions in QMS and Non-QMS Organizations - Derwin Chandra; Bisma Jatmika Tisnasasmita; Hastuti Naibaho (PT. Alahyan Publisher Sukabumi, 2026)
This study examines differences in employee perceptions of organizational adaptive responses to external pressures between organizations with and without formal quality management systems (QMS). A quantitative comparative cross-sectional design was employed. Data were collected from 211 employees across QMS and non-QMS organizations in Indonesia using a 26-item closed questionnaire on a five-point Likert scale and analyzed via independent-samples t-tests. Four hypotheses were tested across regulatory, industry, customer pressure, and internal process adjustment dimensions. All four hypotheses were statistically supported (p < 0,001). QMS organizations consistently recorded higher mean scores, with the largest aggregate gap on regulatory pressure (Δ = 0.87) and the smallest on industry pressure (Δ = 0.27). Item-level analysis revealed that readiness for government inspection (TR5) produced the largest gap across all 26 items (Δ = 1.14), while two items, competitive pressure (TI3) and customer-related rule adjustment (RA4), showed negative gaps where non-QMS organizations scored marginally higher. This study extends open systems and institutional perspectives by demonstrating that QMS influences adaptive responses differently across pressure dimensions. The identification of negative-gap anomalies challenges linear assumptions in adaptation theory, suggesting that formal systems may trade consistency for flexibility in specific operational contexts. This study examines differences in employees' perceptions of an organization's adaptive response to external pressures between organizations that have and do not have a formal quality management system (QMS).